The management of post-traumatic stress disorder and associated pain and sleep disturbance in refugees. (7th March 2019) - Lies, July; Jones, Lester; Ho, Roger
SUMMARY: More than 68 million people worldwide have been forcibly displaced and one-third of these are refugees. This article offers an overview of the current literature and reviews the epidemiology and evidence-based psychological and pharmacological management of post-traumatic stress disorder (PTSD), sleep disturbance and pain in refugees and asylum seekers. It also considers the relationship between sleep disturbance and PTSD and explores concepts of pain in relation to physical and psychological trauma and distress. During diagnosis, clinicians must be aware of ethnic variation in the somatic expression of distress. Treatments for PTSD, pain and sleep disturbance among refugees and asylum seekers are essentially the same as those used in the general population, but treatment strategies must allow for cultural and contextual factors, including language barriers, loss of freedom and threat of repatriation. LEARNING OBJECTIVES: After reading this article you will be able to: recognise the challenges faced by the large number of refugees worldwide understand the relationship between PTSD, sleep disturbance and pain in refugees broadly understand the evidence for psychological and pharmacological therapy for treating PTSD, sleep disturbance and pain in refugees. DECLARATION OF INTEREST: None.